Optimalisasi Persediaan Bahan Baku Kemas dengan Metode Program Dinamis Algoritma Wagner Within - Alim Setiawan Slamet; Eka Kresno Dianti (Jurnal Manajemen dan Organisasi, 2022)
Inventory is a very important role for a company especially manufacturing industry. Good inventory control is needed to manage inventory to be effective and efficient. This research held at PT XYZ because there are some problems such as overload warehouse and overstock inventory. The purpose of this research is to analyze packaging material inventory to get the optimal inventory with warehouse capacity constraint. Primary data were obtained through observation at Pulogadung warehouse, interview with related divisions, and secondary data were obtained from company documents. Data were analyzed by Material Requirement Planning with Wagner Within Algorithm Dynamic Program Method. The result of this research show that Wagner Within Algorithm dynamic program can decrease the expand of the company beside the exist method the company used. Some implementation impacts of silver meal dynamic program are the availability of materials when they needed and warehouse is not overloaded.